Asian Men’s Health: Gender Disparity and Life Expectancy. - Ho, Christopher CK; Teo, Chee Hau; Ng, CJ; Zulkifli MZ; Tan, MH (Department of Surgery, UKM Medical Centre, 2014)
The aim of this review was to analyze the gender disparities found as well as the life expectancies in Asia. An analysis of the data on gender disparities as well as life expectancies of the different Asian countries was done based on the World Health Organization (WHO) Global Health Observatory Data Repository as well as the regional government databases. Middle Eastern countries have the highest male to female population ratio. The results show that in terms of population pyramid, Asia is moving towards a more geriatric population. Qatar has the highest life expectancy for men and is the only country in Asia where men live longer than women (difference of 2 years). In general, women in Asia live longer than men. High income countries like Hong Kong, Japan and Singapore have higher life expectancies as compared to those on the lower income nations. The life expectancy of Asian men still lags women. Men’s health care needs to be addressed urgently. The disparity in income-status reflecting the lifespan of men is an impetus for us to narrow the gap of health in Asian countries.